Vulneración al debido proceso en el procedimiento administrativo - Bossio Davila, Hector Paul (2019)
ABSTRACT Due process is the right of every person to initiate or participate in a process or procedure, within the guarantees established to fundamental rights, which are provided by the general principles of law and procedural law. This right requires for its application a direct participation of the state through its imperium faculty, which using the legal norm and its repressive nature that is the ius puniendi to sanction all those who commit crimes and at the same time violate any protected legal right by the rules. This is where the Due Process, in reality, is a principle that is not defined or detailed as a concrete procedural norm. Regarding its content and scope, however, it has a profound legal significance in procedural or procedural matters. Between the Due Process and the presence of Human Rights, are practically concepts that are closely linked, because as mentioned in the previous paragraph, due process is a fundamental right, subjective and public that contains a set of guarantees : procedural principles and procedural rights, which the parties have in the process. The fulfillment of due process guarantees the effectiveness of the right to effective judicial protection, since these guarantees, procedural principles and rights are nummerus apertus, taking as a parameter the legal assessment of justice and human dignity, in other words, they are all those parameters that consign the human being as the center of society and its coexistence within a State of Law.